Dampak Positif Ekonomi sebagai Hasil Tata Kelola Destinasi yang Berkelanjutan di Desa Kutuh Kawasan Pantai Pandawa – Bali - Lemy, Diena Mutiara; Jun, Kim Min; Tjang, Madeline Stefanie; Lei, Wu Lei (Jurnal Master Pariwisata (JUMPA); Volume 07, Nomor 02, Januari 2021, 2021)
The purpose of this research paper to identify the impact of sustainable tourism management towards the economic conditions of a community. In 2018, Pandawa Beach has won first rank for Indonesia Sustainable Tourism Awards (ISTA) in the field of economic utilization to local communities hence the author decided to use Pandawa Beach for the research. The qualitative data were collected from interviews and the quantitative data were collected from questionnaires. The method for analyzing the data is using descriptive analysis. The research result shows that sustainable tourism gives positive impacts towards the economic conditions on Kutuh Village. 72 people out of 90 are satisfied with the current economic welfare of the local community. The data is also valid because the AVE and CR results are all above 0.7 which means the results are acceptable. Keywords: sustainable tourism management, economic impact of tourism, Pandawa Beach Bali